2002
DOI: 10.1080/11250000209356472
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure ofOctopus vulgaris(Mollusca, Cephalopoda) from the Mediterranean Sea as revealed by a microsatellite locus

Abstract: Citing articles: 13 View citing articles Ital. J. Zool., 69-295-300 (2002) ABSTRACT An investigation of the genetic variability of Octopus vulgaris, an intensively harvested species, was carried out using a microsatellite locus as genetic marker. Samples from one eastern Atlantic and nine Mediterranean locations were analysed. In each population, the number of alleles at locus Ov06 varied from four to seven and was 21 overall. Observed and expected heterozygosity values ranged from 0.310 to 0.655 and 0.506… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
2
24
0
3
Order By: Relevance
“…Population-level studies within octopods for the most part have used microsatellite markers and have focused on commercial species such as Octopus vulgaris Casu et al 2002;Murphy et al 2002;Oosthuizen et al 2004;Cabranes et al 2008;Moreira et al 2011;Zuo et al 2012), Macroctopus maorum (Doubleday et al 2009), Octopus pallidus (Higgins and Burridge 2012), Octopus maya (JuĂĄrez et al 2010) and Octopus minor (Zuo et al 2011;Kang et al 2012a) although markers have also been developed (Strugnell et al 2009b(Strugnell et al , 2009c to attempt to answer broader questions about connectivity (e.g. Strugnell et al 2012).…”
Section: Incirratamentioning
confidence: 98%
“…Population-level studies within octopods for the most part have used microsatellite markers and have focused on commercial species such as Octopus vulgaris Casu et al 2002;Murphy et al 2002;Oosthuizen et al 2004;Cabranes et al 2008;Moreira et al 2011;Zuo et al 2012), Macroctopus maorum (Doubleday et al 2009), Octopus pallidus (Higgins and Burridge 2012), Octopus maya (JuĂĄrez et al 2010) and Octopus minor (Zuo et al 2011;Kang et al 2012a) although markers have also been developed (Strugnell et al 2009b(Strugnell et al , 2009c to attempt to answer broader questions about connectivity (e.g. Strugnell et al 2012).…”
Section: Incirratamentioning
confidence: 98%
“…Mature female individuals often migrate from shallow reef flats into deeper subtidal areas for spawning (Oosthuizen and Smale, 2003;Smale and Buchan, 1981;Whitaker et al, 1991). Upon hatching, planktonic larvae move into the water column for one to two months, and dispersal is thought to be wide ranging with larvae travelling up to several hundred kilometres in ocean currents (Murphy et al, 2002;Casu et al, 2002). Thus it is likely that spawning females contribute to the maintenance and replenishment of stocks at a regional level, not simply in the vicinity of the spawning locality.…”
Section: Introductionmentioning
confidence: 96%
“…The evidence of significant population structuring among the sampled populations reported here is not unique for octopuses. Most studies of population genetics within octopuses report significant population structure among groups [11,13,15]. This is not surprising due to the relatively sedentary nature of adult octopuses.…”
Section: Resultsmentioning
confidence: 98%
“…Several microsatellite markers have been isolated and characterized for the common octopus, Octopus vulgaris, [11] and used to evaluate the genetic structure of its populations along the northwest coast of Africa [12], the Mediterranean Sea [13], the Iberian Peninsula and the Canary Islands [14], and off the coast of Brazil [15]. All of these studies have reported relatively high genetic diversity and most report significant population structuring among sampled groups.…”
Section: Introductionmentioning
confidence: 99%